Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae) - Schintlmeister, Alexander; Irungbam, Jatishwor Singh (Zootaxa, 2019)
A new notodontid species, Euhampsonia rubricata spec. nov., is described from NW India and W Myanmar and compared to its eastern sister species E. sinjaevi Schintlmeister, 1997. The female genitalia of the latter are illustrated for the first time. A full synonymic list of the genus Euhampsonia is provided.